ANALISIS PENERAPAN AUGEMENTED REALITY PADA PEMBELAJARAN ALAT MUSIK PIANO MENGGUNAKAN UEQ - Victoria Angela Sugianto; Suyoto Suyoto (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2023)
Generally, musical instrument learning is done face-to-face, with a teacher providing examples and later instruction from students follows. Many people want to learn the piano because the piano is able to express itself, one of which is for choir or personal pleasure. When someone plays the piano without any instruction from a teacher or someone who is an expert in playing the piano, they tend to use the wrong technique and posture in playing the instrument. Augmented Reality (AR) technology  has been widely used to facilitate the learning of new skills. In this study, it proposes a comparative analysis of applications that have applied Augmented Reality  technology using testing scenarios and using  the User Experience Questionnaire (UEQ) method. In this study, data collection was carried out by comparing  the Perfect  Piano application and the Skoove: Learn Piano  application using questionnaires. The questionnaire was distributed offline with a target of 10 respondents then divided into 2 groups based on the application to be studied. The results of this study show that the Perfect Piano application  has a value of 5.43 which is higher than  the Skoove: Learn Piano application.  This shows that  the Perfect Piano  application is easier for someone to use to learn the piano. This research is expected to be used to facilitate future research, especially to create an application that is more interactive and can be used as a means to facilitate musical instrument learning.